Controversial aspects of diagnostics and therapy of idiopathic condylar resorption: an analysis of evidence- and consensus-based recommendations based on an interdisciplinary guideline project - Riechmann, Merle; Schmidt, Christopher; Ahlers, M. Oliver; Feurer, Ima; Kleinheinz, Johannes; Kolk, Andreas; Pautke, Christoph; Schön, Andreas; Teschke, Marcus; Toferer, Astrid; Lux, Christopher J.; Kirschneck, Christian; et al. (Journal of Clinical Medicine, 2023)
Idiopathic condylar resorption (ICR), though a rare event, is associated with severe detrimental sequelae for the patient. To date, the etiology remains unknown, and treatment strategies are highly controversial. Therefore, the aim of this study is to present an analysis of the consensus- and evidence-based approach to ICR by a German interdisciplinary guideline project of the AWMF (Association of the Scientific Medical Societies in Germany). Following a systematic literature search, including 56 (out of an initial 97) publications, with a predominantly low level of evidence (LoE), two independent working groups (oral and maxillofacial surgery and interdisciplinary, respectively) voted on a draft comprising 25 recommendations in a standardized anonymized and blinded Delphi procedure. While the results of the votes were relatively homogeneous, the interdisciplinary phase required a significantly higher number of rounds (p < 0.001). Most of the controversial recommendations were related to initial imaging (with consensus on CT/CBCT as the current diagnostic standard for imaging), pharmacotherapy (no recommendation due to lack of evidence), discopexy (no recommendation possible due to low LoE) and timing of orthognathic surgery (with consensus on two-staged procedures after invasive TMJ surgery, except for single-stage procedures if combined with total joint reconstruction). Overall, the Delphi procedure resulted in an interdisciplinary guideline offering the best possible evidence- and consensus-based expertise to date in the diagnosis and treatment of ICR.
Veröffentlicht: 27. Juli 2023
Gesehen am 10.10.2023